Comparative Study of Biomethane Purification Process using Analytical Hierarchy Process - Putri, Theodora Mega; Simanjuntak, Berlian; Rumahorbo, Eyunike; Panggabean, Kristy (Politeknik Negeri Malang, 2025)
The selection of purification technology for upgrading biogas to biomethane involves complex considerations, as each technology -such as pressure swing adsorption (PSA), membrane separation (MS), or chemical absorption (CA) - offers distinct advantages and disadvantages. The Analytical Hierarchy Process (AHP), provides a systematic framework to simplify and resolve such complexities. This research aims to apply AHP to critically compare purification technologies for biomethane. AHP method is implemented in four steps which includes determination of AHP structure (goal, criteria, sub-criteria and alternatives), formation of pairwise comparison matrices based on literature study and expert opinion, normalization and consistency calculation, and prioritization of alternatives. The criteria considered in AHP analysis of this study are technology capacity, cost, and environmental impact. Overall, PSA received the highest weight for state of technology. In terms of separation performance, CA achieved the highest scores for methane purity and methane retention. From a cost and environmental impact perspective, MS performed best. However, despite its advantages, MS application is limited by its relatively lower maturity and limited scalability. By evaluating alternatives based on AHP framework, PSA was identified as the top-priority option, with total weight score of 0.426, followed by MS with total weight score of 0.387 and CA with total weight score of 0.181. This study has successfully demonstrate the application of AHP to select purification technologies for converting biogas to biomethane.